2021
DOI: 10.1155/2021/1925388
|View full text |Cite
|
Sign up to set email alerts
|

Microhardness and Fluoride Release of Glass Ionomer Cement Modified with a Novel Al+3 Complex to Enhance Its Antimicrobial Activity

Abstract: Objectives. To synthesize and characterize a novel Al+3 complex with 2-(2-hydroxyphenyl)-1H-benzimidazole (HL) to be added to a restorative glass ionomer cement (GIC) to enhance its antimicrobial activities and to evaluate the Vickers microhardness (HV) and fluoride release (FR) of the modified GIC. Materials and Methods. Al+3 complex was synthesized by the addition of 1 mmol (0.210 g) of HL to 1 mmol (0.342 g) of aluminum sulfate in ethanol. The resulting solution was then refluxed under stirring for 24 h and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The negative values of the activation entropies ΔS* imply a more ordered activated complex than the reactants and/or the reactions are slower than typical. [ 49 ] The high activation energy values (ΔE*) show that the chelates under consideration are highly stable. The positive values of ΔG* indicated that this was a non‐spontaneous process.…”
Section: Resultsmentioning
confidence: 99%
“…The negative values of the activation entropies ΔS* imply a more ordered activated complex than the reactants and/or the reactions are slower than typical. [ 49 ] The high activation energy values (ΔE*) show that the chelates under consideration are highly stable. The positive values of ΔG* indicated that this was a non‐spontaneous process.…”
Section: Resultsmentioning
confidence: 99%
“…2-(2-Hydroxyphenyl)-1H-benzimidazole (HPBI; Figure 1 A) was purchased from Sigma-Aldrich (Darmstadt, Germany), while Al−HPBI complex ( Figure 1 B) was synthesized and characterized in our previous study [ 26 ]. Both compounds (HPBI and Al−HPBI complex) were dissolved first in 5 mL of 100% dimethylformamide (DMF), and then the volume was adjusted to 100 mL using sterilized distilled water to make a 5 mM stock solution.…”
Section: Methodsmentioning
confidence: 99%
“…After coating, each specimen was stored in remineralizing solution (0.02 M HEPES, 1.8 mM KH 2 PO 4 , 3.0 mM CaCl 2 , 130 mM KCl; pH 7.0) [ 29 , 30 , 31 ] at 37 °C for 7 or 28 days. These storage periods were defined on the basis of the amount of fluoride released from fluoride-containing materials (mainly glass ionomer cement) [ 32 , 33 , 34 ]. From day 7, the amount of released fluoride was not large.…”
Section: Methodsmentioning
confidence: 99%